2006
DOI: 10.1007/s10535-005-0068-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of phytohormones in organogenic ability of elm multiplicated shoots

Abstract: The study presents the comparative analyses of endogenous contents of auxin (IAA), cytokinins (CKs), polyamines (PAs), and phenolic acids (PhAs) in apical and basal parts of elm multiplicated shoots with regard to the organogenic potential. The shoot-forming capacity was higher in the apical part than in the basal part. However, the timing of root formation was in the apical type of explant significantly delayed (compared with the organogenic potential of basal part). Significantly higher contents of free base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
6
12
0
3
Order By: Relevance
“…It is generally known that high concentrations of endogenous IAA has an important role in root initiation. In analogy to our results, higher IAA contents were found in basal shoot parts of Ulmus glabra Huds [41] and Centaurium erythraea [42]. In addition to IAA content, we also found that the activity of IAAO was reduced remarkably (Figure 3A), which might correspond to the rise in endogenous IAA levels, confirming previous results [43].…”
Section: Discussionsupporting
confidence: 92%
“…It is generally known that high concentrations of endogenous IAA has an important role in root initiation. In analogy to our results, higher IAA contents were found in basal shoot parts of Ulmus glabra Huds [41] and Centaurium erythraea [42]. In addition to IAA content, we also found that the activity of IAAO was reduced remarkably (Figure 3A), which might correspond to the rise in endogenous IAA levels, confirming previous results [43].…”
Section: Discussionsupporting
confidence: 92%
“…Shoots in an early developmental stage did not produce roots, suggesting that root formation is more dependent on shoot developmental stage than on the media composition. The rooting of P. vulgaris shoots without addition of auxins was also reported by Clapa et al [11] and despite being unclear why this species does not require auxins for rooting, the obtained results could be due to high levels of endogenous auxins in shoots, as previously reported in other species [17]. This suggests that the development of a more efficient protocol should be directed to obtain a larger number of shoots, without compromising shoot viability, since the rooting phase does not have to be optimized.…”
Section: Shoot Proliferation and Rootingsupporting
confidence: 78%
“…For example Centeno et al (2003) observed that the temporal accumulation of CKs is involved in the initiation of cell division, while the maintenance of auxins levels is related to the long-term callus development. Furthermore, Malá et al (2005) found that the higher contents of free bases and ribosides of isoprenoid CK in multiplicated shoots is the most important factor for shoot formation. In our experiments the induction of organogenesis on T tobacco leaf segments placed on medium with an excess of isoprenoid cytokinins (Z or DHZ), exhibited a higher shoot formation compared to the regeneration on segments of WT tobacco leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Z may be degraded by the enzyme cytokinin oxidase/dehydrogenase (CKX; Armstrong 1994), or inactivated by N-glycosylation when catalysed by N-glucosyltransferases (Vaňková 1999;Hou et al 2004), or ribosylation or ribophosphorylation when catalyzed by CK non-specific adenylate metabolizing enzymes (Sondheimer and Tzou 1971;McGaw et al 1984;Moffatt et al 1991;McGaw and Burch 1995;Allen et al 2002). The physiological activity of each form of isoprenoid CK during in vitro shoot organogenesis is related to the interconversion and rapid turnover of their different forms (Malá et al 2005). The formation and metabolism of particular forms of cytokinins described their quantity, but not necessarily activity.…”
Section: Introductionmentioning
confidence: 99%